Pengadaan Aplikasi Online Arsip Vital Keluarga Cerdas (ARVIGADAS) oleh Pemerintah sebagai Sarana Pencegah Sengketa Tanah dalam Masyarakat Pasca Terjadinya Bencana: Array - 1 (Arsip Nasional Republik Indonesia, 2021)
Damage or loss of vital records is one of the impacts that occurred after the disaster that occurred in Indonesia. In this paper, it will be recommended an online application procurement called ARVIGADAS (Smart Family's Vital Archive Application), an application that serves to store the results of the media transfer of the family's vital archive. The procurement of this application aims to prevent one of the problems that occur due to loss or damage to the family's vital archive, namely land disputes due to loss or damage to land certificates as proof of land ownership. The procurement of applications and the transfer of archive media is carried out based on the existing legal archives.